Photovoltaic panels efficiency on the ships - Popa, Ciprian; Popescu, Mihai-Octavian; Târhoacă, Mircea; Popa, Nicolae-Silviu (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In this paper, the main goal was to integrate photovoltaic panels in the power generation systems of ships in the marine environment in order to reduce pollution and make energy consumption more efficient. Taking into account the route of the ship with the help of which the experimental data was taken at 3 photovoltaic panels and thanks to the navigation equipment through which the parameters of the hydrometeorological conditions were extracted from the entire research period, the main influences of the environment on the obtained electrical yield were analyzed. This work directly contributes to future optimizations in terms of integration of solar power generation systems in the marine environment.